Penguatan Kecakapan Komunikasi Publik Santri Melalui Program Khitobah: Strengthening Public Communication Skills of Islamic Boarding School Students Through the Khitobah Program - Nasyidatu Ruhaniah; Khoerotunisa Khoerotunisa; Ahmad Saefudin (Al-Musannif, 2025)
The skill of public speaking is crucial for everyone in this era of informational globalization. Therefore, Islamic boarding schools, as cultivators of Muslim generations, must be capable of developing and discovering a public communication skills development system. This research aims to analyze the implementation of khitobah in developing students' public communication skills, which also has implications for improving students' social and religious behavior. The object of this qualitative research is the Al-Qonitat Miftahun Najah Tahunan Jepara Islamic Boarding School. Informants consisted of managers, teachers, and students who were selected purposively. Data was collected using observation, interviews, and documentation techniques. Data analysis uses descriptive analysis techniques. The research results show that the implementation of the khitobah has fulfilled the elements of management. The khitobah program not only strengthens students' public communication skills but also improves social and religious behavior, such as empathy, social involvement, and strengthening interpersonal relationships. This research has implications for the importance of Islamic boarding schools including subjects or activities that support the development of public communication skills in their curriculum. Apart from that, it is also necessary to educate the public to change perceptions about the role and function of Islamic boarding schools in providing comprehensive education to students, including non-religious aspects such as developing communication skills.